Study the Tribological Properties of PEEK/PTFE Reinforced with Glass Fibers and Solid Lubricants at Room Temperature (International Journal of Current Engineering and Technology, 2014)
Investigations of tribological properties of polymers and polymers with filler materials, the present work has been carried out by using pin on disk. Normal load, velocity and atmospheric temperature these parameters were considered for tests. The friction and the wear mechanisms of PEEK based composites under dry condition was studied for non lubricated reciprocating compressor piston rings.. Base polymeric materials poly-ether-ether-keton (PEEK) containing fillers (PTFE) and solid lubricants like MOS2, Bronze reinforced with Glass were investigated. Composite Pins of (1)PEEK+ PTFE (wt15%) + glass fibers (wt15 %), (2) PEEK+PTFE (wt15%) + glass fibers (wt15 %)+Mos2(wt 5%), (3) PEEK+ PTFE (wt15%) + glass fibers (wt15 %)+Mos2(wt 5%), +Bronze (wt15%), (4) PEEKPTFE (wt15%) + glass fibers (wt15 %)+Mos2(wt 5%), +Bronze (wt 20 % ). were tested against disk of grade EN-8 with an initial surface roughness of 0.4 micron. In all tests, conducted on pin-on- disk and wear data collected by machine analyzed, the following conclusion can be drawn: friction and wear in polymers are fundamentally different from the mechanism which occurs in metals. A very important conclusion on wear resistance of polymers and composites is its strong dependence on the atmosphere and normal load. It is observed that wear rate of PEEK+PTFE (wt15%) +glass fiber(wt 15% shows very high, it was 9.44x10-11mm3/NM and friction coefficient 0.133. but adding 5% MoS2 in PEEK/PTFE reinforced with glass fibers shows wear rate 3.31x10-11 mm3/NM and friction coefficient 0.015.By adding bronze15%wt in PIN-3, 20% wt in PIN-4, wear rate was 2.98x10-9 mm3/NM and 8.075x10-11 mm3/NM respectively. It means by increasing the percentage of bronze in PEEK/PTFE reinforced with glass fibers, it minimize the wear. Among the tested of materials, the PEEK with fillers like PTFE, glass fibers, MoS2, Bronze have shown the greatest sliding wear resistance.
Keywords: PEEK/PTFE , Glass fiber , solid lubricants, Tribological properties